Effects of Nonthermal Plasma (NTP) on the Growth and Quality of Baby Leaf Lettuce (Lactuca sativa var. acephala Alef.) Cultivated in an Indoor Hydroponic Growing System - Giulia Carmassi; Fatjon Cela; Alice Trivellini; Francesca Gambineri; Lamberto Cursi; Antonio Cecchi; Alberto Pardossi; Luca Incrocci (Horticulturae, 2022)
The aim of this research was to develop an effective protocol for the application of nonthermal plasma (NTP) technology to the hydroponic nutrient solution, and to investigate its effects on the growth and quality of baby leaf lettuce (Lactuca sativa var. acephala Alef.) grown in a hydroponic growing system (HGS) specifically designed for indoor home cultivation. Four HGSs were placed in separate growth chambers with temperature of 24 ± 1 °C and relative humidity of 70 ± 5%). Lettuce plants were grown for nine days in nutrient solutions treated with NTP for 0 (control) to 120 s every hour. Results of the first experiments showed that the optimal operating time of NTP was 120 s h−1. Fresh leaf biomass was increased by the 60 and 120 s NTP treatments compared to the control. Treating the nutrient solution with NTP also resulted in greater leaf content of total chlorophylls, carotenoids, total phenols, and total antioxidant capacity. NTP also positively influenced chlorophyll a fluorescence in Photosystem I (PSI) and photosynthetic electron transport. These results revealed that the NTP treatment of the nutrient solution could improve the production and quality of hydroponically grown baby leaf lettuce.